Síntese e caracterização de catalisadores nanométricos de LaSrNiO4 para aplicação em dessulfurização de tiofeno - Sousa, Karla Silvana Menezes Gadelha de (2009)
The mixed metal oxides constitute an important class of catalytic materials widely investigated in different fields of applications. Studies of rare earth nickelates have been carried by several researchers in order to investigate the structural stability afforded by oxide formed and the existence of catalytic properties at room temperature. So, this study aims synthesize the nanosized catalyst of nickelate of lanthanum doped with strontium (La(1-x)SrxNiO4-d; x = 0,2 and 0,3), through the Pechini method and your characterization for subsequent application in the desulfurization of thiophene reaction. The precursor solutions were calcined at 300ºC/2h for pyrolysis of polyester and later calcinations occurred at temperatures of 500 - 1000°C. The resulting powders were characterized by thermogravimetric analysis (TG / DTG), surface area for adsorption of N2 by BET method, X-ray diffraction (XRD), scanning electron microscopy (HR_SEM) and spectrometry dispersive energy (EDS). The results of XRD had show that the perovskites obtained consist of two phases (LSN and NiO) and from 700ºC have crystalline structure. The results of SEM evidenced the obtainment of nanometric powders. The results of BET show that the powders have surface area within the range used in catalysis (5-50m2/g). The characterization of active sites was performed by reaction of desulfurization of thiophene at room temperature and 200ºC, the relation F/W equal to 0,7 mol h-1mcat -1. The products of the reaction were separated by gas chromatography and identified by the selective detection PFPD sulfur. All samples had presented conversion above 95%